Russian anti-literature - Hellebust, Rolf (University of Nottingham, 2013)
To support the myth of Russian literature’s unique social mission, its critics, historians, and creators since the time of Pushkin have used various strategies to present it as inherently nomoclastic – as somehow standing apart from established European models (e.g. Tolstoy’s preface to War and Peace), or otherwise distinguished from more trivial forms of writing designed primarily for entertainment rather than education (e.g. Chernyshevsky’s What Is to Be Done?) In the efforts of nineteenth-century Russia to realize its cultural ambitions the yardstick was always Western Europe; yet these efforts could only be judged successful if grounded in a concept of the nation’s uniqueness. Therefore, the social function that was to mold Russia’s destiny could only arise from a literature that measured itself against the West and yet remained distinct – one that could be seen as an antithesis to the Western cultural establishment just as young Russia as a whole sought to see itself as old Europe’s opposite. At the same time, the anti-literary strategies of Russian writing (from the genre-breaking labels of Pushkin’s Evgeny Onegin and Gogol’s Dead Souls to the defiantly ‘bad’ prose of Chernyshevsky) serve to compensate for the impossible burden of redemptive expectation, by means of deferring the final expression and perfection of both its form and content.